T MAJONI MR: Conceptualization of The Influence of Entrepreneurship Education on Developing Entrepreneurial Intention for Industrialisation of Zimbabwe: A case study of graduates from Zimbabwean State Universities - Tasara Majoni; Professor Maria Tsvere; Dr Shepherd Murebwa (Journal of Social Science, 2023)
Research on entrepreneurship education has grown across the globe but less focus is given to its influence on developing entrepreneurial intentions for industrialisation. Research focus focused on the influence of entrepreneurship education on entrepreneurial intentions in general. The prime objective of this paper therefore is to essentially explore the influence of entrepreneurship education on developing entrepreneurial intentions for industrialisation. The study used mixed methodology. Majorly, four theories of entrepreneurship were used namely: Schumpeterian Entrepreneurship Theory, Ajzen’s Theory of Planned Behaviour (TPB), Experiential learning theory, Capital Resources Theory and Social Cognitive Career Theory (SCCT). The findings indicate that entrepreneurship education is essential for building entrepreneurial intentions for industrialisation. Specifically, results indicate that entrepreneurship education influences graduates to start wanting to engage into entrepreneurial activities for industrialisation, start deciding to develop own innovations, determined to engage into entrepreneurial activities, start considering to engage into entrepreneurial activities, start hoping to engage into entrepreneurial activities and start to wish to engage into entrepreneurial activities. The paper also lucidly shows that entrepreneurial intentions influences graduates to Start their ventures, to develop innovations, to produce goods and services and to develop patents. In addition, the influence of entrepreneurship education on industrialisation is positively mediated by entrepreneurial intentions for industrialisation and moderated by institutional and government support factors. Hence, it is echoed that institutions of higher learning need to prepare students for industrialisation through entrepreneurship education. The government should support entrepreneurship education through government funding and further training. Institutions of higher learning should support entrepreneurship education through instilling entrepreneurship culture in students, providing financial support and entrepreneurship education modules which cultivates entrepreneurship in students. In conclusion, the importance of entrepreneurship education as a significant component for propelling entrepreneurial intention for industrialisation and industrialisation cannot be underestimated. It is thereby suggested that, higher institutions of learning should offer entrepreneurship education in order to develop entrepreneurial intentions for industrialisation and actual industrialisation of a country.